Iron deficiency anemia: An insight into new screening parameters - Gaurav Chhabra; Samanyoya Gochhait (Wolters Kluwer Medknow Publications, 2017)
Iron deficiency anemia is the most prevalent nutritional deficiency disorder in India. Diagnosis of iron deficiency can sometime be quite tricky due to discordant biochemical results obtained in presence of other chronic disorders or due to biological variations. There is certainly a need of newer markers which could help in the early identification of iron deficient states particularly in resource limited set up. Technological advancements have made it possible with the availability of new red cell parameters along with the traditional CBC parameters, which when fully utilized can aid in the screening & diagnosis of iron deficiency anemia.